Bulgaria : Financial Sector Assessment Program: Technical Note. (IMF Staff Country Reports; Country Report ;, 2017)
This Technical Note examines the current state of nonperforming loans (NPLs) in Bulgaria and makes recommendations for a strategy to substantially reduce NPLs. The Bulgarian National Bank should adopt a comprehensive strategy in the near term to achieve a substantive reduction in NPL levels over a three- to five-year time horizon. The strategy should focus on more intensive measures to enhance bank practices in three main areas: (1) loan loss provisioning; (2) loan write-downs of NPLs, in whole or in part, where collection is unlikely; and (3) collateral valuation. This effort would be supported further by enhanced supervisory guidance, supervisory reporting, and risk disclosure.